2018
DOI: 10.1371/journal.pone.0207411
|View full text |Cite
|
Sign up to set email alerts
|

Activation of trigeminal ganglion satellite glial cells in CFA-induced tooth pulp pain in rats

Abstract: This study further investigated the mechanisms underlying the rat model of tooth pulp inflammatory pain elicited by complete Freund’s adjuvant (CFA), in comparison to other pulpitis models. Pulps of the left maxillary first molars were accessed. In the CFA group, the pulps were exposed, and CFA application was followed by dental sealing. In the open group, the pulps were left exposed to the oral cavity. For the closed group, the pulps were exposed, and the teeth were immediately sealed. Naïve rats were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Recently, CFA has been frequently used to study pulpal pain (Matsuura et al 2013, Filippini et al 2018, Watase et al 2018. Further, a rapid onset of definitive pain was observed.…”
Section: Cfa-induced Inflammation and Nociceptive Behaviourmentioning
confidence: 99%
“…Recently, CFA has been frequently used to study pulpal pain (Matsuura et al 2013, Filippini et al 2018, Watase et al 2018. Further, a rapid onset of definitive pain was observed.…”
Section: Cfa-induced Inflammation and Nociceptive Behaviourmentioning
confidence: 99%
“…CFA is a mixture of mineral oils containing heat‐inactivated Mycobacterium tuberculosis, which has been widely used to induce chronic inflammatory pain when injected into the rat tooth pulp 16,17 . CFA induced pulpitis is a developmental process, including the development of pulpitis to apical periodontitis and alveolar bone inflammation, as well as the repair process of inflammatory injury at the later stage.…”
Section: Resultsmentioning
confidence: 99%
“…The studies found that after applying complete Freund's adjuvant (CFA) to induce pulpitis, macrophages were activated in the TG. The innervation of single TG neurons to multiple pulps was involved in enhancing the activity of TG neurons in adjacent non inflammatory teeth, resulting in ectopic persistent dental pulp pain 16 . Therefore, the interaction between activated macrophages and neurons in the TG may be the key to regulate pulpitis pain and repair of nerve injury.…”
Section: Introductionmentioning
confidence: 99%
“…It is now well known that activation, proliferation, and inflammatory signaling in microglia and astrocytes within the TN and SGCs within the TG are important mechanisms for the maintenance of pathological orofacial pain, as demonstrated using preclinical pain models [127]. More than 20 years ago, Byers and colleagues found a marked upregulation of GFAP staining in the TG after pulp injury, and the work has been replicated by other groups [45,128]. The increased expression of activated satellite glia cells in the TG, as measured by GFAP expression, can occur adjacent to the neurons innervating the injured or inflamed pulp, as well as neurons innervating adjacent, non-injured teeth [113,129].…”
Section: The Effect Of Pulp Injury On Glial Changes In the Tg And Tnmentioning
confidence: 93%